PENGENDALIAN PERSEDIAAN TEPUNG TAPIOKA (25 KG) PADA CV. CIPTA KARYA MANDIRI SAMARINDA (Studi Empiris Pada Perusahaan periode 2016) - Wibowo, Muhammad Rico Tri (EKONOMIA, 2018)
MUHAMMAD RICO TRI WIBOWO, Control of Tapioca Flour Stock (25Kg) at CV. Cipta Karya Mandiri Samarinda under the guidance of Mr. Eddy Soegiarto as the first director and Ms. Rina Masyitoh Haryadi as the second director.Supervision and maintenance of supplies is an important problem in an organization in every economic sector. Inventory arises due to the synchronous demand with the provision of time used to process raw materials to maintain the balance of demand with the supply of raw materials and processing time required by supply. Inventory is very important because if the supply material arrives late until it runs out it will affect the profits that will be obtained by the company even consumers will look for products in other places, this will have a very bad impact on the company because it cannot serve and look after consumers well.The purpose of this study was to analyze the inventory and minimize the cost of tapioca flour supply on the CV. Cipta Karya Mandiri Samarinda ..The problems in this are as follows: "What is the supply of Tapioca Tepung (25kg) on the CV. Cipta Karya Mandiri in Samarinda is optimal? "The analytical tool used to analyze inventory control is using the EOQ method (Economic Order Quantity), to calculate the reorder point using ROP (Reorder Point), to calculate inventory costs using TIC (Total Incremental Cost).The results of the analysis mention the CV. Cipta Karya Mandiri has not been optimal in order quantity to order tapioca flour in one order with an order quantity of 4,668 sacks with one year order frequency which is 6 times, while according to calculation EOQ method is 8,617 sacks with a frequency of ordering in one year which is 4 times and calculation of booking costs based on the company of Rp. 19,086,007.94 while the calculation using EOQ is Rp. 17,642,362.35 there is a difference in inventory costs of Rp. 1,443,645,59. If the company uses the EOQ method, the company can save on inventory costs of Rp. 1,443,645,59.The fewer the ordering frequency, the lower the inventory costs the company will incur.